Remoção de fenilalanina por adsorvente produzido a partir de torta prensada de grãos defeituosos de café - Helia Luiza Marques Clark (2010)
Defective coffee beans press cake, a residue from biodisel production based on coffee oil, was evaluated as raw material in the production of an adsorbent for phenylalanine removal. Batch adsorption studies were conducted at 25, 35 and 45 °C. The effects of particle size, adsorbent dosage, contact time, initial pH and initial concentration of phenylalanine were investigated. Preliminary adsorption tests pointed toward the needfor chemical activation to increase adsorption capacity. Such tests also demonstrated that nitrogen flow during activation had a negative effect on adsorption capacity because of loss of surface chemical groups. Phenylalanine adsorption was favored by a reduction in adsorbent particle size. The effect of initial pH was evaluated in the rangeof 2 to 10, indicating that low pHs hinder adsorption as a result of electrostatic repulsion. Adsorption equilibrium was attained after 6 h for all the evaluated phenylalanine concentrations. Langmuir, Freundlich, Tempkin, Dubinin-Redushkevich (D-R) and Henderson models were tested for equilibrium description, with Langmuir providing the best fit. Adsorption kinetics were evaluated according to the following models: pseudo first and second order, reversible first order, Elovich, Ritchie and intraparticle diffusion. The pseudo-second order model provided the best description of the experimental data. The process was found to be exothermic and spontaneous, with chemical and physical forces involved. The results obtained in this study show that defective coffee beans press cake can be viewed as a potential candidate for the production of low cost adsorbents for phenylalanine removal, thus contributing for theimplementation of sustainable development in both the coffee and biodiesel production chains.Key-words: adsorption; activated carbon; defective coffee beans; phenylalanine.